On-design pre-optimization and off-design analysis of hybrid Brayton thermosolar tower power plants for different fluids and plant configurations. (March 2020) - Merchán, R.P.; Santos, M.J.; Heras, I.; Gonzalez-Ayala, J.; Medina, A.; Hernández, A. Calvo
Abstract: A working fluid performs a Brayton cycle that is fed by a heat input from a solar power tower and from a combustion chamber, which burns natural gas. This hybrid system is described by a complete model that includes all the main losses and irreversibility sources (optical and thermodynamic). Numerical implementation and validation is performed based on a Spanish commercial plant. On-design computations are carried out varying the pressure ratio for four working fluids (dry air, nitrogen, carbon dioxide, and helium), for different number of stages and for recuperative and non-recuperative configurations. When adjusting the pressure ratio, an improvement of about 7 % in overall thermal efficiency is predicted for a dry air single-stage recuperative configuration with respect to a standard commercial gas turbine. A study about the main energy losses in each plant subsystem for some particular plant layouts is accomplished. A two-compression and expansion stages recuperative Brayton cycle working with air is expected to give overall thermal efficiencies about 0.29  at design conditions, which is about a 47% increase with respect to the simplest single-stage configuration. It is stressing that fuel consumption from the reheaters maybe higher than that of the main combustion chamber for multi-stage layouts. Off-design hourly curves of output records for the four seasons throughout a day are analyzed. Greenhouse emissions are also analyzed. Specific carbon dioxide emissions are smaller for helium than for dry air, when they both work in a single-stage non-recuperative configuration. Highlights: A comprehensive full model of a hybrid thermosolar plant is presented. Solar, combustion, and power block subsystems are described in detail. Numerical results are obtained for a commercial-size plant. Several working fluids for the power block are analyzed. Single-stage and multi-stage Brayton cycles are studied. There are a wide variety of configurations that make these systems a priori commercially interesting.